PEMANFAATAN MEDIA SOSIAL TIKTOK UNTUK PEMASARAN BISNIS DIGITAL SEBAGAI MEDIA PROMOSI - Deden Sunandar; Devi Wardiyanti (Jurnal Ekonomi dan Bisnis, 2025)
Nowadays, people use TikTok as a creative means to convey various information. The aim of this research is to identify how @institut_banten utilizes TikTok in marketing their digital business. This research uses a qualitative observation method with a descriptive approach, as well as data collection techniques through interviews and documentation. Data analysis was carried out after data collection through interviews and then stored in depth in documentation. Observation results show that @institut_banten has used social media, especially Instagram, to promote their business, which has had an impact on increasing the number of followers and increasing awareness of their products. Apart from Instagram, TikTok accounts are also used as a promotional tool to attract customers on social media, which has the potential to increase their monthly income.